Upaya Pengelolaan Penyakit Diabetes Melitus Dengan Pendekatan Dokter Keluarga - Noviana Zara; Henny Putri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2023)
A 52 year old male patient with complaints of weakness in the body. Initially the patient was brought to the Health Center with complaints of weakness since 3 days. Weakness is felt suddenly throughout the body and feels continuously. Complaints of weakness are also accompanied by a feeling of dizziness in the head. The patient also complained of frequent urination at night, urinating more than 10 times in one night. The patient also constantly feels thirsty, but his appetite has decreased since the last 2 years or so. The patient feels a loss of weight. In addition, the patient also complained of a wound on his left leg which had not healed since 1 year ago. Primary data were obtained through anamnesis and physical examination by conducting home visits, filling out family folders, and filling out patient files. The assessment was carried out based on the initial holistic diagnosis, process and end of the visit both quantitatively and qualitatively. Patients and families are given education about diabetes mellitus including the symptoms and complications that will arise, education about the patient's motivation to take medication regularly as well as educating and teaching patients about foot care and diabetes exercise. An approach with family doctor intervention is able to improve habits that are influential in the treatment of diabetes mellitus.